Analisis Nilai Tambah Davocas (Dates Avocado Seed) Dalam Mendukung Pengembangan Agroindustri Pangan Berbasis Biji Alpukat Dan Biji Kurma - Ahmad Haris Hasanuddin Slamet; Muhammad Edwinsyah Yanuan Putra; Fanecia Apriani (Universitas Negeri Gorontalo, 2026)
Davocas (Dates Avocado Seed) is an instant boba product made from avocado seeds and date seeds combined with various flavored sauces. This article aims to analyze the added value of processing avocado seeds and date seeds into Davocas using the Hayami method and formulate its development direction as a micro-scale agro-industrial product. The study uses a quantitative descriptive approach based on prototype production data. The Hayami analysis includes input, output, conversion factor, labor coefficient, output value, contribution of other inputs, added value, labor income, profit, and margin distribution. The analysis results showed that processing 40 kg of raw materials into 20 kg of Davocas produces a conversion factor of 0.50. At an output price of IDR 175,000/kg and contribution of other inputs of IDR 26,000/kg, the output value is IDR 87,500/kg, added value is IDR 61,500/kg, and the value-added ratio is 70.29%. Profit reaches IDR 59,000/kg with a profit level of 95.93%. These results indicated that Davocas has high added value potential because its main raw materials come from low-value by-products.